"If somebody just showed me once how to do it": How are workplace cultures and practice development conceptualised and operationalised for early career nurses?. (February 2020) - Daws, Karen; McBrearty, Katherine; Bell, Deborah
Abstract: Background: An imminent nursing shortage mandates attention to retention of early career nurses. One factor that impacts on intention to stay in the profession is the ability to do the work. Early career nurses rely on supportive cultures to develop the practical skills and knowledge specific to particular workplaces. Objectives: This study was conducted to determine the impact of workplace culture on practice development for early career nurses. Methods: We undertook a qualitative study using semi-structured interviews conducted with eleven early career nurses at a single metropolitan hospital in Melbourne, Australia. Interviews were transcribed verbatim and analysed using thematic analysis techniques. Results: Themes identified were learning in the moment, active welcome, confidence, ambiguities in the culture of learning, bullying and navigating the space. Conclusions: Early career nurses conceive practice development as the acquisition of skills and knowledge particular to the immediate needs of their patients, which they learnt by asking questions. Developing confidence was integral to all aspects of practice development. Complexity and risk on the wards could negatively impact on confidence. Where welcome was explicit and overt the nurses felt that practice development was facilitated. Transition to practice programs supported nurses and some individual nurses were active in assisting nurses to develop. However, workplace cultures were at times indifferent to the learning needs of the early career nurses and some experienced poor workplace behaviour and bullying.